In MODEL PROJECT CITIZEN UNTUK PENGUATAN CIVIC LITERACY RESOLUSI KEKERASAN DI KAMPUS - Zaenul Slam (Institut Pendidikan Tapanuli Selatan, 2024)
Campuses as a vehicle for character education are apparently not sterile from cases of sexual violence as a result of weakening civic literacy. This research aims to find out how civic literacy in sexual violence resolution is developed through the Project Citizen (PC) model. This research uses a case study method to examine the problem of sexual violence and solve it. The research data was obtained by observation, interviews, and exploration of portfolio documents in the broadcast section and documentation section. The research results show that the PC model can develop civic literacy in sexual violence resolution for students. Apart from that, the PC model can provide independence, mutual cooperation, responsibility, critical and creative students. It is recommended to maximize the project citizen model as a learning model that can strengthen various civic literacy